Impact of the COVID-19 pandemic: Insights from vacation rentals in twelve mega cities. (November 2021) - Liang, Shuai; Leng, Hong; Yuan, Qing; Yuan, Chao
Abstract: Coronavirus disease 2019 (COVID-19) is a challenging global problem. COVID-19 has caused shocks to various urban systems, and the tourism industry is no exception. We analyzed the impact on vacation rentals by conducting diachronic data mining on nearly 10 GB of rental data (calendar, listings, and reviews) in twelve highly internationalized megacities distributed across Asia, Europe, America, and Oceania based on the data set from the Inside Airbnb website. All twelve cities were adversely affected. The specific time of the impact is related to the pandemic's outbreak and enforced lockdowns policies. Affected by the epidemic, reservation rates decreased, tourists preferred renting in suburbs instead of city centers, the proportion of foreign tourists in all destinations dropped sharply, tourist sentiment scores fluctuated dramatically especially among foreigners, and people focused less on tourism related activities. This study reveals the changing illustrations of vacation rentals in highly internationalized megacities under the pandemic's influence. It offers a methodological assessment framework to monitor the hospitality sector over time and aims to serve as a reference for preparedness in similar cities worldwide.